Patient-specific atrial hemodynamics of a double lumen neonatal cannula in correct caval position - Muhammad, Jamil; Rezaeimoghaddam, Mohammad; Çakmak, Bilgesu; Rasooli, Reza; Salihoğlu, Ece; Yıldız, Yahya; Pekkan, Kerem (Wiley, 2018)
Clinical success of pediatric veno-venous (VV) extracorporeal membrane oxygenation (ECMO) is associated with the double lumen cannula cardiovascular device design as well as its anatomic orientation in the atrium. The positions of cannula ports with respect to the vena cavae and the tricuspid valve are believed to play a significant role on device hemodynamics. Despite various improvements in ECMO catheters, especially for the neonatal and congenital heart patients, it is still challenging to select a catalogue size that would fit to most patients optimally. In effect, the local unfavorable blood flow characteristics of the cannula would translate to an overall loss of efficiency of the ECMO circuit. In this study, the complex flow regime of a neonatal double lumen cannula, positioned in a patient-specific right atrium, is presented for the first time in literature. A pulsatile computational fluid dynamics (CFD) solver that is validated for cardiovascular device flow regimes was used to perform the detailed flow, oxygenated blood transport, and site-specific blood damage analysis using an integrated cannula and right atrium model. A standard 13Fr double lumen cannula was scanned using micro-CT, reconstructed and simulated under physiologic flow conditions. User defined scalar transport equations allowed the quantification of the mixing and convection of oxygenated and deoxygenated blood as well as blood residence times and hemolysis build-up. Site-specific CFD analysis provided key insight into the hemodynamic challenges encountered in cannula design and the associated intra-atrial flow patterns. Due to neonatal flow conditions, an ultra high velocity infusion jet emanated from the infusion port and created a zone of major recirculation in the atrium. This flow regime influenced the delivery of the oxygenated blood to the tricuspid valve. Elevated velocities and complex gradients resulted in higher wall shear stresses (WSS) particularly at the infusion port having the highest value followed by the aspiration hole closest to the drainage port. Our results show that, in a cannula that is perfectly oriented in the atrium, almost 38% of the oxygenated blood is lost to the atrial circulation while only half of the blood from inferior vena cava (IVC) can reach to the tricuspid valve. As such, approximately 6% of venous blood from superior vena cava (SVC) can be delivered to tricuspid. High values of hemolysis index were observed with blood damage encountered around infusion hole (0.025%). These results warrant further improvements in the cannula design to achieve optimal performance of ECMO and better patient outcomes.
13th International Conference on Pediatric Mechanical Circulatory Support Systems and Pediatric Cardiopulmonary Perfusion -- SEP 28-30, 2017 -- Rome, ITALY
WOS: 000430277400007
PubMed ID: 29572879
Keywords: Extracorporeal Membrane Oxygenation; Double Lumen Neonatal Cannula; Blood Residence Time; Hemolysis Index; Computational Fluid Dynamics